Microwave Absorbing Material Using Rubber Wood Sawdust - Se, Sian Meng; Shaaban, Azizah; Mohd Ibrahim, Imran (IEEE, 2011)
Abstract - A flat microwave absorber working at frequency 1.8GHz was developed by impregnation of activated carbon and polyurethane. The activated carbon is prepared from the conversion of rubber wood sawdust through chemical activation process using ZnCl2 solution as the precursor agent. The process involves leaching, heating and washing. The impregnation ratio between ZnCl2 and rubber wood sawdust were at 1:1, 1.5:1 and 2:1. All samples are heated at temperature of 500o C for 60 minutes. It was found that the chemical activation at impregnation ratio of 2:1 produced high purity activated carbons with 79 percent carbon content. Based on the BET analysis, the surface area of the powder for impregnation ratio 1.5:1 reported highest value of 1301 m2 /g, this formulation is selected for making microwave absorber and it was reported that the reflection loss is recorded 10dB at 1.8 GHz.